A Single Base Insertion in F9 Causing Hemophilia B in a Family of Newfoundland–Parti Standard Poodle Hybrid Dogs - Henrike Kuder; Liubov Sandzhieva-Vuzzo; Alexandra Kehl; Jonathan M. Rappaport; Elisabeth Müller; Urs Giger (Genes, 2021)
Hemophilia B is an x-linked recessive hereditary coagulopathy that has been reported in various species. We describe a male Newfoundland–Parti Standard Poodle hybrid puppy and its family with hemophilia B from clinical manifestations to the molecular genetic defect. The index case presented for dyspnea was found to have a mediastinal hematoma, while surgical removal and transfusion support brought some relief, progressive hematoma formations led to humane euthanasia. Sequencing the F9 exons revealed a single nucleotide insertion resulting in a frameshift in the last exon (NM_001003323.2:c.821_822insA), predicted to result in a premature stop codon (NP_001003323.1:p.Asn274LysfsTer23) with a loss of 178 of 459 amino acids. The unexpected high residual plasma factor IX activity (3% to 11% of control) was likely erroneous, but no further studies were performed. Both the purebred Newfoundland dam and her sister were heterozygous for the insertion. Five additional male offspring developed severe hemorrhage and were hemizygous for the F9 variant and/or had a prolonged aPTT. In contrast, other male littermates had normal aPTTs and no evidence of bleeding. While they are related to a common Newfoundland granddam, the prevalence of the pathogenic variant in the Newfoundland breed is currently unknown. These clinical to molecular genetic studies illustrate that precision medicine is achievable in clinical companion animal practice.